Development of injectable cell delivery systems for high accuracy cell therapy applications - Amer, Mahetab H. (2017)
Cell-based therapeutic interventions are being developed for a variety of clinical indications, including irreversible retinal pathologies and stroke. Numerous cell therapy procedures use injection-based administration to deliver high density cell preparations, either systemically or directly. The mode of delivery of fragile cells can compromise treatment efficacy, which is dependent on cell viability and functionality post-injection. Reviewing current literature, there is a lack of comprehensive testing of the effects of injection-based cell delivery on the various parameters of cell function. This study investigated the effects of the administration process on a range of cell characteristics, and aimed to answer critical questions regarding possible reasons for failure to deliver a sufficient numbers of viable cells. Biomaterial-assisted cell delivery was also investigated to determine improvement of cell recovery and possible influence on cell fate.